Perancangan Sistem Informasi Penerimaan Peserta Didik Baru Berbasis Web Pada Mi Madinatunnjah - Rizal Pahlevi; Perani Rosyani (JURIKOM (Jurnal Riset Komputer), 2021)
Mi Madinatunnajah is an educational institution founded by Drs. KH. Mahrus Amin and Hj. Suniyati Abdul Manaf who has the desire to provide Islamic education services to the community as well as possible. In carrying out educational activities, where the process of accepting new students is still by waiting for parents who want to register their children in front of the school gate or still manually so it is very inefficient. To overcome the problems above, it is necessary to build a system that is able to handle data management processes and various other processes so that new student admission services can be more optimal and able to present outputs, both in the form of information and reports accurately and easily. This Web-Based New Student Admission Information System was built using the codeigniter framework, PHP programming language and MySQL database. This application system handles data processing in the form of new student coalon data. This application system can provide convenience for Mi Madinatunnajah in processing data and is able to improve performance and service processes for prospective student.